1987
DOI: 10.1016/s0022-5347(17)43271-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Adenocarcinoma and End Stage Kidney Disease

Abstract: The association of end stage kidney disease with cystic degeneration and renal adenocarcinoma was first recognized in 1977. Since then a number of reports have confirmed this relationship. Duration of dialysis has been the most strongly associated risk factor. We report 8 cases of end stage kidney disease and renal adenocarcinoma. Median duration of hemodialysis was approximately 1 year, and 3 patients never had hemodialysis. Factors other than duration of dialysis, such as toxic metabolites, toxins from dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Previous reports suggested that bilateral RCC occurred in 5–36% of HD patients and multifocal tumors occurred in 60–80% of HD patients 15,17–19 . In our present study, 18% of patients had bilateral RCC, whether synchronous (6%) or metachronous (12%), and 44% of those had multifocal RCC.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous reports suggested that bilateral RCC occurred in 5–36% of HD patients and multifocal tumors occurred in 60–80% of HD patients 15,17–19 . In our present study, 18% of patients had bilateral RCC, whether synchronous (6%) or metachronous (12%), and 44% of those had multifocal RCC.…”
Section: Discussionsupporting
confidence: 59%
“…Previous reports suggested that bilateral RCC occurred in 5-36% of HD patients and multifocal tumors occurred in 60-80% of HD patients. 15,[17][18][19] In our present study, 18% of patients had bilateral RCC, whether synchronous (6%) or metachronous (12%), and 44% of those had multifocal RCC. There is a question whether both kidneys should be removed in patients with ESRD and with a tumor on one side only that has been diagnosed by computed tomography, especially during a scheduled kidney transplantation.…”
Section: Discussionsupporting
confidence: 47%
“…Even in patients with renal cell carcinoma, only 14% reveal symptoms. The high incidence of renal cell carcinoma with no or few symptoms and the quite large number (17.6%) of metastatic renal cell carcinoma cases [52] justify the institution of a regular kidney screen ing program in dialysis patients, especially as reports of such metastatic forms are on the increase [22,52,[62][63][64][65][66], Screening of dialyzed kidneys would be aimed at ascer taining the presence or absence of acquired cysts and detecting the presence of renal cell carcinoma. During screening, it can be fairly well assumed that kidney size after more than 3 years of hemodialysis is a reflection of the severity of cystic change [2], Therefore, even though there may be no cysts visible by CT scan, if the density of the kidney is lower than that of normal renal parenchyma and its size is greater than that expected for the duration of dialysis, then it may contain numerous small, histolog ically distinguishable acquired cysts [38].…”
Section: Screening Acquired Cystic Disease Patients For Renalmentioning
confidence: 99%
“…There was a 3 to 1 male predominance, higher than in the general population but less than had been previously reported in ESRD (2 1,93). Bilateral RCC was documented in seven cases (36, 104,108,120,124).…”
Section: Table 6 Summary Of 108 Cases Of Renal Cell Carcinoma In Patmentioning
confidence: 99%